Personalised medicine in asthma: from curative to preventive medicine. (3rd January 2017) - Guilleminault, Laurent; Ouksel, Hakima; Belleguic, Chantal; Le Guen, Yannick; Germaud, Patrick; Desfleurs, Emilie; Leroyer, Christophe; Magnan, Antoine
The concept of asthma has changed substantially in recent years. Asthma is now recognised as a heterogeneous entity that is complex to treat. The subdivision of asthma, provided by "cluster" analyses, has revealed various groups of asthma patients who share phenotypic features. These phenotypes underlie the need for personalised asthma therapy because, in contrast to the previous approach, treatment must be tailored to the individual patient. Determination of the patient's asthma phenotype is therefore essential but sometimes challenging, particularly in elderly patients with a multitude of comorbidities and a complex exposure history. This review first describes the various asthma phenotypes, some of which were defined empirically and others through cluster analysis, and then discusses personalisation of the patient's diagnosis and therapy, addressing in particular biological therapies and patient education. This personalised approach to curative medicine should make way in the coming years for personalised preventive and predictive medicine, focused on subjects at risk who are not yet ill, with the aim of preventing asthma before it occurs. The concept of personalised preventive medicine may seem a long way off, but is it really? The personalised curative approach in asthma should make way for personalised preventive and predictive medicine http://ow.ly/4nfq2w